Implementasi Nilai-Nilai Ekonomi Islam dalam Program Kerja KKN UINSU di Desa Naga Raja, Kecamatan Sipispis, Kabupaten Serdang Bedagai - Muhammad Hasbi Ansyari; Muhammad Fathi Farhat; Ferdi Gunawan Siagian (Lembaga Pengembangan Kinerja Dosen, 2026)
Community service is a concrete manifestation of the role of higher education institutions in disseminating knowledge and instilling noble values ​​in the wider community. This article describes the application of Islamic economic values ​​in the implementation of the Student Community Service Program (KKN) of the State Islamic University of North Sumatra, held in Naga Raja Village, Sipispis District, Serdang Bedagai Regency. Using a participatory approach, students were actively involved in community economic activities by integrating the principles of justice, honesty, cooperation, and empowerment as the main foundation. Various activities were carried out to raise public awareness of economic practices in accordance with Islamic values, such as ethical micro-enterprise management, the habituation of wise consumption patterns, and the introduction of a sharia-based financial system. The results of the program implementation showed an increase in community understanding and positive attitudes toward Islamic economic concepts, especially in efforts to strengthen economic independence and improve family welfare. Furthermore, community involvement in joint activities also strengthened social solidarity and a sense of collective responsibility. This article emphasizes the importance of the sustainability of Islamic value-based community service programs that are not only educational but also able to encourage sustainable community economic empowerment and oriented towards social justice.